Borrowed Forms The Music and Ethics of Transnational Fiction - Lachman, Kathryn (Liverpool University Press, 2014)
Borrowed Forms examines the use of music by contemporary novelists and critics from across the Francophone, Anglophone, and Hispanophone worlds. Through readings of Nancy Huston, Maryse Condé, J. M. Coetzee, Assia Djebar, Julio Cortázar, and other late twentieth-century novelists, the book shows how writers deploy musical strategies to expand the possibilities of the novel in response to the demands of transnational citizenship. The book transcends disciplinary boundaries, to reveal the entanglement of musical and narrative forms in ethical, historical, and political questions.Critics from Mikhail Bakhtin to Edward Said established musical forms as an indispensable framework for understanding the novel. This study argues that the turn to music in late twentieth century fiction is linked to new questions of authority and representation, as writers seek to democratize the novel, to bring marginalized voices into fiction, to articulate increasingly hybrid subjectivities, and to negotiate the conflicting histories of the diverse groups that make up today's multicultural societies. The book traces the influence of four musical concepts on theory and the contemporary novel: polyphony, or the art of combining multiple, equal voices; counterpoint, the carefully regulated setting of one voice against another; variations, the virtuosic exploration of a given theme; and opera, the dramatic setting of a story to a musical score. Borrowed Forms is both a vital reference for all those seeking to understand the influence of music on 20th-century literary theory, and a rigorous and interdisciplinary framework for considering the transnational novel.